Diagnostics and management approaches for Acanthamoeba keratitis. (2nd July 2020) - Szentmáry, Nóra; Shi, Lei; Daas, Loay; Seitz, Berthold
ABSTRACT: Introduction: With less than 3 new cases per million people, Acanthamoeba keratitis (AK) is an orphan disease. It is a potentially devastating ocular infection without standardized guidelines for diagnostics and treatment. Areas covered: A comprehensive Pubmed and Clinical Trial search has been performed to summarize current diagnostics and management approaches for AK before March 2020. Ophthalmologists must recognize its clinical signs, such as gray-dirty epithelium, pseudodendritiformic epitheliopathy, perineuritis, multifocal stromal infiltrates, and ring infiltrate for a timely adequate treatment. In later stages, scleritis, iris atrophy, anterior synechiae, secondary glaucoma, mature cataract, and chrorioretinitis are referred to as classical clinical signs. A clinical suspicion must be followed by laboratory diagnostics using confocal microscopy, polymerase-chain-reaction (PCR), microbiological culture, and/or histopathological examination. The first randomized clinical drug trial for the treatment of AK is planned to be completed in 2021. Expert opinion: Up to date, as conservative treatment up to 1 year, triple-topical therapy (polyhexamethilen-biguanide, propamidine-isethionate, neomycin) and, in therapy-resistant cases, surgical treatment in form of corneal cryotherapy, riboflavin-UVA crosslinking and penetrating keratoplasty is used. In our opinion, a specific medical treatment should be clinically applied in the future, following isolation of the pathognomic Acanthamoeba strain, and after in vitro culturing and testing.